Identifying "Exclusionary Agreements": Agreement Type as a Procedural Limitation in UNCLOS Dispute Settlement. (26th May 2021) - Roberts, Hayley
Abstract: The United Nations Convention on the Law of the Sea (UNCLOS) is heralded as a constitution for the oceans and, as part of this, provides for a compulsory dispute settlement procedure entailing binding decisions. However, case law and academic commentary have highlighted significant issues in definitively identifying other agreements that could preclude these compulsory procedures—a concept permitted by the Convention in certain circumstances. This article begins to explore this challenge by contending that the type of agreement plays a significant role in whether or not it could be determined to be an "exclusionary agreement." In doing so, the article conducts a systematic interpretation of Articles 281 and 282 UNCLOS, underpinned by the application of relevant provisions in the Vienna Convention on the Law of Treaties. This provides a conclusive basis as to whether the status of an agreement as an "ad hoc agreement" (specific; adopted for the dispute) or an "existing agreement" (general; adopted prior to the dispute) holds any significance in the context of these articles.